Don't like ads? PRO users don't see any ads ;-)

# Untitled

By: a guest on May 1st, 2012  |  syntax: None  |  size: 0.79 KB  |  hits: 20  |  expires: Never
Text below is selected. Please press Ctrl+C to copy to your clipboard. (⌘+C on Mac)
1.    g (Y g) 4
2.    (λfn.(1, if n = 0; and n·(f(n-1)), if n>0)) (Y g) 4
3.    (λn.(1, if n = 0; and n·((Y g) (n-1)), if n>0)) 4
4.    1, if 4 = 0; and 4·(g(Y g) (4-1)), if 4>0
5.    4·(g(Y g) 3)
6.    4·(λn.(1, if n = 0; and n·((Y g) (n-1)), if n>0) 3)
7.    4·(1, if 3 = 0; and 3·(g(Y g) (3-1)), if 3>0)
8.    4·(3·(g(Y g) 2))
9.    4·(3·(λn.(1, if n = 0; and n·((Y g) (n-1)), if n>0) 2))
10.    4·(3·(1, if 2 = 0; and 2·(g(Y g) (2-1)), if 2>0))
11.    4·(3·(2·(g(Y g) 1)))
12.    4·(3·(2·(λn.(1, if n = 0; and n·((Y g) (n-1)), if n>0) 1)))
13.    4·(3·(2·(1, if 1 = 0; and 1·((Y g) (1-1)), if 1>0)))
14.    4·(3·(2·(1·((Y g) 0))))
15.    4·(3·(2·(1·((λn.(1, if n = 0; and n·((Y g) (n-1)), if n>0) 0))))
16.    4·(3·(2·(1·(1, if 0 = 0; and 0·((Y g) (0-1)), if 0>0))))
17.    4·(3·(2·(1·(1))))
18.    24